Sistem Rekomendasi Wisata Pantai menggunakan Metode Simple Additive Weighting - Suherman Suherman; Sunny Samsuni; Imam Lukman Hakim (ILKOM Jurnal Ilmiah, 2020)
The number of beach tourism in the Serang Regency or Anyer beach region and the diversity of the desires of every tourist, then tourists are required knowledge of traveling in terms of choosing the desired tourist location. For tourists who already have the experience of traveling on the Anyer beach, it is not too difficult to determine the desired tourist location, but most tourists who do not have the tourist experience on the Anyer beach will have difficulty being able to determine the expected beach tourism location. This study aims to provide recommendations of 24 Anyer beach tourist attractions to tourists. Recommendations generated using the Simple Additive Weighting (SAW) method using 12 criteria. The results of this study are in the form of applications that can be accessed online. The application can produce appropriate recommendations for tourists in the form of alternative beach tourism along with details such as the name of the beach tour, address, coordinates of Google Maps, photos of the state of beach tourism and the price of admission.